2010
DOI: 10.1371/journal.ppat.1000804
|View full text |Cite
|
Sign up to set email alerts
|

YfiBNR Mediates Cyclic di-GMP Dependent Small Colony Variant Formation and Persistence in Pseudomonas aeruginosa

Abstract: During long-term cystic fibrosis lung infections, Pseudomonas aeruginosa undergoes genetic adaptation resulting in progressively increased persistence and the generation of adaptive colony morphotypes. This includes small colony variants (SCVs), auto-aggregative, hyper-adherent cells whose appearance correlates with poor lung function and persistence of infection. The SCV morphotype is strongly linked to elevated levels of cyclic-di-GMP, a ubiquitous bacterial second messenger that regulates the transition bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
343
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(375 citation statements)
references
References 90 publications
26
343
0
6
Order By: Relevance
“…The robust biofilms formed by K. pneumoniae yfiR cells are most probably due to enhanced polysaccharide production, triggered by local level c-di-GMP that can activate BcsA cellulose synthases. This is similar to what has been reported for both E. coli and P. aeruginosa, where homologues of yfiRNB have been shown to be involved in EPS production and biofilm formation (Malone et al, 2010;Raterman et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The robust biofilms formed by K. pneumoniae yfiR cells are most probably due to enhanced polysaccharide production, triggered by local level c-di-GMP that can activate BcsA cellulose synthases. This is similar to what has been reported for both E. coli and P. aeruginosa, where homologues of yfiRNB have been shown to be involved in EPS production and biofilm formation (Malone et al, 2010;Raterman et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Psl expression is also important for reduced phagocytosis (20). In line with this, increased immune evasion of ΔyfiR mutant strains has been reported, and it has been shown that disruption of pel and psl in a ΔyfiR mutant strain renders it as sensitive to phagocytosis by macrophages as the wild type (14).…”
Section: Discussionmentioning
confidence: 69%
“…Among the RSCV variants found in chronic lung infections are strains harboring loss-of-function mutations in wspF and yfiR, resulting in derepression of the di-guanylate cyclases WspR and YfiN, respectively. This in turn leads to increased production of the regulator molecule c-di-GMP and thereby increased production of biofilm matrix components, as well as a hyperadherent and autoaggregative phenotype (14,15). The occurrence of RSCVs has been correlated with increased risk of failure of antipseudomonal treatment (16).…”
mentioning
confidence: 99%
“…As a strong link between c-di-GMP and the SCV phenotype exists, Malone and colleagues hypothesized that the SCV phenotype of the yfiR mutant was the result of upregulation of TpbB activity due to release of YfiR-mediated repression. The cellular concentration of c-di-GMP measured in the yfiR mutant displayed a significant increase in c-di-GMP when compare to wild type; this observation coupled with the results demonstrating DGC activity of purified TpbB (lacking the transmembrane domain) support the hypothesis that YfiR represses the DGC activity of TpbB (Malone, 2010). Epistasis experiments were performed to determine the regulatory interplay of YfiB, YfiR, and TpbB.…”
Section: P Aeruginosa Environmental Lifestyle and Virulence 59mentioning
confidence: 60%
“…Three independent insertions were mapped to yfiR, the first gene of a predicted three-gene operon yfiBNR (Malone, 2010). YfiR is a periplasmic protein, previously identified as a suppressor of the tpbA mutant phenotype (Ueda, 2009a).…”
Section: P Aeruginosa Environmental Lifestyle and Virulence 59mentioning
confidence: 99%